POTENTIAL IRON AND VITAMIN C FROM MORINGA LEAVES AS A FOOD PRODUCT TO OVERCOME ANEMIA: SYSTEMATIC REVIEW - Hapsari, Martina Widhi; Parameswari, Genoveva Visi; Novianingrum, Milka Putri (Fakultas Sains dan Teknologi, Universitas Nasional Karangturi, 2025)
Anemia is a significant global health problem, especially in developing countries, with a high prevalence among adolescents and pregnant women. This study explores the potential of Moringa (Moringa oleifera) leaves as a nutrient source rich in iron and vitamin C to address anemia. Moringa leaves contain iron up to 7 mg per 100 g and vitamin C as much as 1,89 mg/g, which plays an important role in increasing hemoglobin levels and absorption of non-heme iron. The method used was a literature study with information analysis from various relevant literature sources. The results show that consumption of moringa leaves in the form of food products, such as biscuits and flour, can significantly increase hemoglobin levels, especially in anemic adolescent girls and pregnant women. The interaction between iron and vitamin C in Moringa leaves supports hemoglobin formation and overall health. Therefore, the integration of moringa into the daily diet can be an effective strategy in preventing and overcoming anemia and improving public health.